Nilai Humanisme dalam Novel 3726 MDPL Karya Nurwina Sari serta Relevansinya sebagai Materi Ajar Sastra di SMA - Alifah Hasna Salsabila; Sumartini Sumartini (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This research is motivated by the urgency of integrating humanistic values into literature learning for character building among students, as well as the lack of scientific studies that thoroughly examine the novel ‘3726 MDPL’ by Nurwina Sari. The purpose of this research is to identify and analyze the humanistic values contained in the novel and to describe its relevance as teaching material in high schools. The study employs a qualitative descriptive method with a case study design, where data is collected thru content analysis and documentation techniques, and then analyzed using the interactive model of Miles, Huberman, and Saldana. The research results show that there are six forms of humanistic values in the novel, namely respecting others opinions, cooperation, caring for others, helping each other, solidarity, and self-sacrifice. These values have significant pedagogical relevance as teaching materials in high school literature because the align the Indonesian Language Learning Outcomes Phase F and the Pancasila Student Profile, particularly in the dimensions of mutual cooperation and global diversity, thus making them an effective medium for fostering empathy and social sensitivity among students.